2014
DOI: 10.1186/1471-2164-15-405
|View full text |Cite
|
Sign up to set email alerts
|

Complete sequences of organelle genomes from the medicinal plant Rhazya stricta(Apocynaceae) and contrasting patterns of mitochondrial genome evolution across asterids

Abstract: BackgroundRhazya stricta is native to arid regions in South Asia and the Middle East and is used extensively in folk medicine to treat a wide range of diseases. In addition to generating genomic resources for this medicinally important plant, analyses of the complete plastid and mitochondrial genomes and a nuclear transcriptome from Rhazya provide insights into inter-compartmental transfers between genomes and the patterns of evolution among eight asterid mitochondrial genomes.ResultsThe 154,841 bp plastid gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 81 publications
(108 reference statements)
2
57
0
Order By: Relevance
“…To isolate mitochondrial sequences from the original Illumina reads, a BLAT (BLAST‐like alignment tool v36) search of forward and reverse reads against a reference database including 41 protein‐coding genes and two rDNA mitochondrial gene regions from the two Gentianales taxa Asclepias syriaca L. (NC_022796) and Rhazya stricta Decne. (NC_024293) was conducted (Straub et al, 2013; Park et al, 2014). Forward and reverse reads were both saved if either showed at least 70% similarity to any of the Gentianales reference sequences.…”
Section: Methodsmentioning
confidence: 99%
“…To isolate mitochondrial sequences from the original Illumina reads, a BLAT (BLAST‐like alignment tool v36) search of forward and reverse reads against a reference database including 41 protein‐coding genes and two rDNA mitochondrial gene regions from the two Gentianales taxa Asclepias syriaca L. (NC_022796) and Rhazya stricta Decne. (NC_024293) was conducted (Straub et al, 2013; Park et al, 2014). Forward and reverse reads were both saved if either showed at least 70% similarity to any of the Gentianales reference sequences.…”
Section: Methodsmentioning
confidence: 99%
“…We used minimap2 to map the enriched PacBio reads against these four sequences, with the expectation that reads spanning the repeat and flanking regions of the alternative configurations with robust mapping quality (MQ > 50) represent actual structural variations present within the sequenced individual tree (e.g. Park et al 2014; Skippington et al 2015; Cole et al 2018; Dong et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…A recent study found that R. stricta extracts promoted apoptosis induction in breast cancer cells, suggesting its potential as an achemo-preventive or therapeutic agent [18,19]. However, currently there have been no genomic resources for R. stricta to facilitate the development of this species for therapeutic applications using a genomic approach on natural product [20][21][22].…”
Section: Introductionmentioning
confidence: 99%